Demand for beef in Malaysia: preference for quantity, quality or lean? - Tey, Yeong Sheng; Shamsudin, Mad Nasir; Radam, Alias; Mohamed, Zainal Abidin; Mahir Abdullah, Amin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
Using the Malaysian Household Expenditure Survey 2004/2005 data, this study investigated Malaysian consumers’ preference for beef quantity, quality, and lean beef. Demand and price models that incorporated consumer socio-economic variables were estimated via two-stage least squares (2SLS). This study showed that Malaysian consumers tend to demand for more quantity rather than quality of beef products. Malaysian consumers are also more responsive to price changes rather than fat reduction in beef products. It is more profitable for beef market players to increase their production as Malaysian consumers are expected to consume increasing amounts of beef products.